Current pharmacotherapy of bradykinin-mediated angioedema. (April 2013) - Farkas, Henriette
<x xml:space="preserve">Abstract</x> Introduction: Bradykinin-mediated angioedema is characterized by subcutaneous and/or submucosal edema formation without wheals and pruritus. It is linked to bradykinin-enhanced vascular permeability and, therefore, it does not respond to conventional measures, but requires specific therapy. Areas covered: This summary briefly reviews the different types of bradykinin-mediated angioedema and its remedies. Therapy focuses on relieving edema, as well as on decreasing its incidence and severity. The modes of the actions of attenuated androgens and antifibrinolytics are not precisely known – these agents have been introduced on an empirical basis. Contemporary treatments, by contrast, have been purposely developed to inhibit bradykinin. Most experience pertains to angioedema resulting from C1-inhibitor deficiency, and the controlled studies have focused on the hereditary form of this disease type (HAE). The pathomechanisms of HAE with normal C1-inhibitor activity, as well as of angiotensin-converting enzyme inhibitor-releated, and of non-histaminergic idiopathic sporadic angioedemas are largely unknown. Appropriate laboratory methods for the diagnosis, or specific interventions for the therapy of these conditions are not available or only available off-label. Expert opinion: In this case, diagnosis and management are challenging. The range of targeted therapeutic options has increased in recent years and includes measures to handle emergencies, prevent edematous episodes and manage additional types of bradykinin-mediated angioedema.